Abortion and well-being: A narrative literature review - Ernestina Coast; Rishita Nandagiri; Andra Fry; Midanna de Almada; Heidi Johnston; Hazal Atay; Bela Ganatra; Antonella Lavelanet; Nurudeen Alhassan; Aduragbemi Banke-Thomas; Lucía Berro Pizzarossa (SSM: Qualitative Research in Health)
“Well-being” is utilised in multiple ways – an everyday word, a component of health, a policy objective, reflecting a diverse set of shifting meanings, conceptualisations, definitions, measurements, and theorising. Influenced by structural and social conditions, well-being can be enhanced or diminished and is experienced at a range of scales (individual, community, society). Globally, abortion is a common practice with implications for well-being. However, the intersections and linkages between abortion and well-being have not yet been explicitly synthesised. To extend understandings, theorising, and measurements, we conducted a systematically searched narrative literature review of evidence pertaining to abortion and well-being.We used a grounded theory-driven approach to theoretically sample items until concept (abortion and well-being) saturation was reached, meaning our study was guided by the literature, rather than imposing an external set of theories. Our database searches (January 01, 2005–June 19, 2023) identified 7665 unique records yielding 753 records for the review, from which n = 167 items were selected for extraction.Our analysis of extracted items yielded four main themes. First, only a minority (13/167) of studies explicitly engaged with well-being. Second, the majority of studies incorporated well-being-allied concepts, without explicitly framing their research as about well-being. We developed insights from these studies using four sub-themes: social connectedness, individual agency, mental health, and physical health. Third, there is limited use of theory and/or frameworks in the empirical evidence. Last, we interrogated the empirical research on abortion and well-being over the life course.Well-being and allied concepts can be useful and productive analytic framings with relevance for research on abortion. We invite readers to consider how these concepts might be used to develop and iterate innovation – methodologically, empirically, and theoretically – to clarify, extend and deepen links between abortion and well-being.